Rural and Urban Language Variation in Balikpapan City: A Sociolinguistic Review: Variasi Bahasa Rural dan Urban di Kota Balikpapan: Tinjauan Sosiolinguistik - Shabrina Shafaa Riawan; Wahyu Akbar Nusantoro Wahyu; Sitti Rahmah; Maulia; Rika Istianingrum (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2026)
This study is motivated by differences in language practices between coastal communities that maintain regional languages and urban student communities that are more open to informal Indonesian, slang, and digital media influence. This research aims to describe rural language variation at Kampung Baru Harbor and urban language variation among students of Universitas Balikpapan, as well as to explain the social factors shaping their differences. This study uses a descriptive qualitative design with a sociolinguistic approach. The data were obtained from natural speech events in two research locations and collected through non-participant observation, listening and note-taking techniques, and documentation of the social context of speech. The analysis was conducted through data reduction, categorization, thematic presentation, and conclusion drawing based on language choice, vocabulary, prosody, code-mixing, communication style, and identity function. The findings show that the rural community uses Bugis as a marker of ethnic solidarity with a direct, loud, fast, and efficient speech style.